Banking Integration on a European Level- Legislation and Supervision - Gummerus, Joe (My University, 2008)
The Banking markets have developed and changed a lot during the past twenty years. At the same time, the legislation on a European level has developed a great deal. The purpose of this thesis is to study the developments in banking legislation and supervision on a European level from the EC treaty in 1957 to this day. In the thesis I have studied the legislation given in the European Union, both primary and secondary legislation. The literature related to the topic has been studied as well. Due to the nature of the study, both older and more recent literature has been taken into account in order to get a full view of the development of the banking legislation and supervision. As references I have also studied working papers and documents prepared by the European Commission and the European Central Bank and national central banks. The speed of the developments in banking regulation and supervision in Europe has been tremendous, especially during the past fifteen years. Also the structures of the regulation have changed towards a more harmonized and efficient legislation. Initially the legislation was more sector oriented, meaning that banks, insurance companies and investment firms were regulated separately. Especially during the past ten years the focus of the regulation has changed towards a more consolidated regulation and supervision. This is especially due to the development of financial conglomerates and the fact that it has been noticed that these conglomerates need to be regulated on a consolidated basis.
Keywords: Banking regulation; Banking supervision; European Union; fi=Talousoikeus|en=Business Law|